2018
DOI: 10.1038/s41405-018-0005-5
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial efficacy of a foam mouthwash and its ability to remove biofilms

Abstract: Objectives/AimsTo evaluate the antimicrobial activity of a newly developed foam mouthwash containing a modified lactoperoxidase system in vitro.Materials and methodsBiofilms of five bacterial species were developed on hydrophobic and hydrophilic surfaces whilst salivary-based biofilm was grown on tooth enamel. Each surface was exposed to the foam mouthwash or saline in vitro. Optical density and scanning electron microscopy (SEM) was used to determine retention of the biofilm following 5 or 30 s exposure time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Volatiles & Essent. Oils, 2020;7(1): 9-17 Karadağ et al DOI: 10.37929/nveo.685474 To prevent oral and dental infections, mouthwash solutions or formulations with antimicrobial activity may prevent but also eliminate pathogenic bacteria (Jones et al, 2018;Müller et al, 2017). However, mouthwashes can affect the oral tissue, the tooth enamel and also deteriorate symptoms if the pH is too acidic, due to ethanol or other compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Volatiles & Essent. Oils, 2020;7(1): 9-17 Karadağ et al DOI: 10.37929/nveo.685474 To prevent oral and dental infections, mouthwash solutions or formulations with antimicrobial activity may prevent but also eliminate pathogenic bacteria (Jones et al, 2018;Müller et al, 2017). However, mouthwashes can affect the oral tissue, the tooth enamel and also deteriorate symptoms if the pH is too acidic, due to ethanol or other compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Single bacteria were mainly detected after 12 h, while aggregate bacteria and micro-colonies dominated the 48 h samples. Other studies that have shown incomplete eradication of oral bacteria in biofilms following the application of photodynamic therapy [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies on the effect of lactoperoxidase on oral microorganisms are being constantly published and document its effects against Streptococcus mutans in caries, when used separately [142,166,167,168,169,170] or in combination with lactoferrin, lysozyme, or immunoglobulins [140,141,171,172,173,174]. The ability of S. mutans to create biofilms have been taken into account together with the activity of glucosyltransferases responsible for the synthesis of exopolysaccharides that build the biofilm matrix [142,166,168].…”
Section: Clinical Applicationmentioning
confidence: 99%
“…The ability of S. mutans to create biofilms have been taken into account together with the activity of glucosyltransferases responsible for the synthesis of exopolysaccharides that build the biofilm matrix [142,166,168]. It has been observed that the mouth rinse foam effectively reduces the retention of biofilms produced by salivary as well as nonpathogenic bacteria of the oral cavity [171]. In addition to S. mutans , studies also concentrate on other oral streptococci [141,167,170], species associated with the occurrence of periodontal disease [141,169,170] and C. albicans fungi [167,173].…”
Section: Clinical Applicationmentioning
confidence: 99%
See 1 more Smart Citation